PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KANTOR DINAS PENDIDIKAN DAN KABUDAYAAN KABUPATEN BATANGHARI - Etty Siswati (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This study is intended to explain the influence of Discipline and work motivation on employee performance in the department's Office of Education and Culture, Batang day.Analissis method used is quantitative method that uses path analysis tool (part analisysis). Testing the significance of the study variables influence employee Discipline (X1) and work motivation (X2) as an independ- ent variable, and employee performance as the dependent variable (Y). Test performed F and t test.The results of hypothesis testing for the effect of variable discipline to employee performance shows that the value of t = 2.503 at 78 degrees and α = 5% greater than the value daari t table = 1.665. This significant effect and variable individual discipline on employee performance. Great influence on the performance of employee discipline is 8.80% (0.088) > The magnitude of the indirect effect of education employees through employee training on job performance is 4.10% (0.041).The results of hypothesis testing for the effect of variable motivation on employee performance showed the value t = 2.163 in the degrees of freedom = 78 and α = 5% greater than the value of the t table = 1.665.The third hypothesis testing results on the influence of variables on the performance of discipline and motivation shows that the value of F count = 11,800 in the degrees of freedom = 77 and α = 5% greater than the value of F table = 3.960.  This means that together there is a significant influence of variables on the performance of discipline and motivation.The amount of influence jointly given by the variables on the performance of discipline and motivation is 0.235 or 23.5 percent of the independent variables are influential or well explain the changes in the performance of employees and 76.5 percent are influenced by other factors not included in the model.Based on these results it can be concluded that the influence of Discipline and motivation together significantly affect employee performanceKeyword: Discipline and Motivation, Office of Education and Culture department, Batanghari.